(untitled) (Revista LIDER, 2020)
The Huasteca is a regional located in the northeast of Mexico, extending from the Gulf Coast to the Sierra Madre Oriental. It is a region mythically famous for its riches. The importance of this territory is famous because of its very ancient history, its ethnic diversity and presence in the Mexican national reality. The Huastecan territory is especially dedicated to the primary sector and, in consequence, it presents important social and economic problems that make this region very por for a large portion of the population. This situation explains why the Huasteca expulses its manual labor force to the United States of American. Such situation generates a series of important problems; for instance, the loss of traditional and ancient knowledge.